Using CT-scanning technology to quantify damage of the stem-boring beetle, Aphanasium australe, a biocontrol agent of Hakea sericea in South Africa. Issue 1 (2nd January 2020) - Lyons, Candice L.; Tshibalanganda, Muofhe; Plessis, Anton Du
ABSTRACT: The stem-boring beetle, Aphanasium australe was introduced into South Africa in 2001 for biocontrol of Hakea sericea . It has a two-year life cycle, the majority of which is spent within the basal stem and roots of its host plant. Damage assessments indicate that A. australe is capable of killing 7-10% of trees in a Hakea stand. However, how much internal damage, and number of insects that are required to cause significant damage or death of the plant, is not known. Here, we used a novel technique – X-ray micro computed tomography (microCT) – to quantify damage in dead and live trees. We also used the technique to assess whether microCT is feasible as a means to determine percentage emergence and survival of larvae/pupae within Hakea stumps. Results showed that the technique can be used successfully to quantify damage, and that felled live trees had significantly less damage than felled dead trees. The amount of internal damage was significantly influenced by the number of insects that emerged, and by the overall size of the trees. MicroCT was able to determine with 100% accuracy the survival of insects that were either inside stumps or had emerged at the time of scanning. A complex suite of factors are responsible for death or survival of trees once infested with the biocontrol agent, and percentage internal damage to trees is not the only factor that dictates whether or not a tree will succumb to the effects of the stem-borer.